Gutter oil, an alternative collector to traditional diesel collector for cleaner flotation of fine coal. Issue 8 (18th April 2021) - Nie, Chun-Chen; Zhu, Xiang-Nan; Wang, Qiang; Lyu, Xian-Jun; Qiu, Jun; Li, Lin
ABSTRACT: In order to realize cleaner production of coal flotation and reduce the dependence of traditional nonrenewable diesel collector, renewable collector was prepared from gutter oil and used for the flotation process. For contrast, flotation performance of gutter oil and traditional diesel collector was analyzed. The functional group composition of the two collectors was compared by infrared spectrum analysis (FTIR). In addition, the adsorption properties of collectors on the particle surface were analyzed by X-ray photoelectron spectroscopy (XPS). Then, flotation experiments were conducted to verify the applicability of renewable collector. FTIR results show that the main functional groups of diesel oil are C-C and C-H, while the gutter oil contains C = O and C-O besides hydrophobic groups, which results in higher ash content of clean coal. XPS results show that the hydrophobicity group content of coal increased significantly after the adsorption of collector. The flotation result show that the ash content of clean coal can be reduced to less than 10% and accompanied by more than 80% combustible matter recovery for both the gutter oil and diesel oil. This study demonstrates that the coal flotation process can become cleaner by using gutter oil as green collector.